(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
bioremediation process, analyzing the effect of temperature to the specific growth values of a remediating microbes on a particular xenobiotic will yield important information that can be translated into the field in future studies. Due to their tiny size, microbes are particularly very sensitive to variations in temperature. Temperature typically influences the growth and metabolic activity of bacterium on the substrates they are grown upon. There are several models that may be utilized to mimic the rate of growth of microbes on a numerous plethora of substrate or media at varying temperatures. Among the most often adopted models is the Arrhenius model, in part because to its minimal parameter number. To study the effect of temperature on Bacillus circulans strain Neni-10 growth on Metanil Yellow, a chevron-like graph with a discontinuous apparent activation energy was observed. The graph’s exhibited a breakpoint at 31.91 °C. Per the regression analysis obtained, the activation energy needed for growth on Metanil Yellow at temperatures ranging between 20 and 30 °C was 62.07 kJ/mol. At temperatures ranging from 35 to 45 °C, its activation energy reduces to 30.93 kJ/mol. At a temperature of 35 °C, the maximum growth rate of the bacterium on Metanil Yellow occurred, and this rate was found to be reduced as the temperature was increased.